Seabed Morphology Mapping for Jack-Up Drilling Rig Emplacement - Faber William M.; Wiwin Windupranata; Dwi Wisayantono (Indonesian Journal of Geospatial, 2017)
Most of the oil and gas potential reserves are located in offshore area. Jack-up drilling rig is one type of many other oil rig type. To locate a jack-up rig, a sea mapping process must be conducted to get information about the seabed surface and what kind of morphology there are. The seabed condition must be clearly identified in order to know if there are any endangering objects or obstructions within the emplacement area, start from the planned maneuver for rig entrance up to the rig's leg penetration.The instruments used are single beam echo sounder, multibeam echo sounder, side scan sonar. Single beam echo sounder have a role to validate the result of the multibeam echo sounder. To know about the existing features, side scan sonar is used to make a high resolution seabed image. Also if the result must be interpreted by a geophysicist. To know about the soil structures, then a soil boring must be conducted to know the site's soil structure. Within the mapping area, there are seven wells are proposed. Single beam and multibeam echo sounder results bathymetric data and side scan sonar results seabed features information. Within the 2kmx2km mapping area there are some area that might be a threat specifically located in the southern and eastern part. Side scan sonar also provides information about the existence of some rock/coral outcrops and high reflectivity seabed that may be an obstruction. Based on the bathymetric, seabed features, and sub-seabed features, the seven proposed wells comply the requirement of jack-up drilling rig emplacement, but based on soil boring data only well four, five, and six comply.